A (IN) EXISTÊNCIA DE UM PROJETO EDUCACIONAL PARA OS NEGROS QUILOMBOLAS NO PARANÁ: DO IMPÉRIO A REPÚBLICA - Padilha, Lucia Mara de Lima (2016)
This thesis aimed at analyzing the public and republican education and the (in) existence of an educational project for Afro- Americans in Paraná, in the historical period defined between the late nineteenth and early twentieth century. From this larger objective elapsed specific ones: to understand the historical context in which they were enslaved and the formation of “Quilombos” in Paraná; investigate when liberal and capitalist ideas started in Paraná as an antagonistic movement to slavery; identify the (in) existence of an educational project for them in Paraná, within the historical period defined. The categories of analysis chosen for this study were: – Contradiction; Class struggle and Wholeness. The method used had, as theoretical and methodological assumption, the Historical and Dialectical Materialism, which involves carrying out an analysis of the totality of the political, economic and social relations present in the society of the period, taking into account that education does not occur in an isolated form but, is part of the human life and is structured to change the way man produces his existence in a material way. The research was developed under a documentary and bibliographical approach and the methodological procedures were as followed: literature review; documentary research and survey of primary and secondary sources about the afro - American population and education in Paraná, located in Parana´s Public Library, House of Memory, Paranaense Museum and Paraná´s Public Archives, Campos Gerais Public Library and Museum in Ponta Grossa. In view of the proposed objectives for this study, this research is constituted of four chapters: in the first chapter, questions about the slavery of the Afro-American and the formation of “Quilombos” in Paraná, as a slavery resistance movement, were addressed; in the second, we sought at investigating when was the beginning of liberal ideas as an antagonistic movement to slavery in Paraná; the third chapter aimed at understanding how was the integration of Afro-American to Paranaense republican society in the post-abolition period, and,in the fourth chapter, the analysis of public education and republican state in Paraná ,as well as the (in) existence of an educational project for negroes in the late nineteenth century and early twentieth century were carried out. Concluding, the thesis defended is that there wasn’t an educational project aimed at the formation of Afro-American children, children of former slaves, in the first decades after the abolition of slavery in Parana.